Dual isomorphic mechanisms and the role of a transnational agent: How foreign MNEs affect environmental innovation in domestic firms. Issue 3 (16th September 2019) - Ha, Yoo Jung; Wei, Yingqi
Abstract : Purpose: Corporate environmental innovation (CEI) is a proactive type of response to increasing public scrutiny regarding firms' environmental performance. While past studies have overwhelmingly focused on coercive mechanisms and assumed a closed national institutional field, less attention has been given to non-coercive and transnational inter-firm mimetic mechanisms. This paper aims to investigate the joint effect of coercive isomorphic mechanisms from domestic institutions and mimetic isomorphic mechanisms from foreign multinational enterprises (MNE) on CEI adoption in domestic firms. Design/methodology/approach: The study's empirical analysis is based on data from 1, 967 firms from the 2010 Korean Innovation Survey, as well as other official statistics. Findings: This study reports the following results: the direct effects of domestic institutions on CEI adoption in domestic firms vary according to institution type; foreign MNEs have a positive effect, whether using global or local CEI strategies; and the positive effect of foreign MNEs strengthens when the stringency of domestic environmental regulation increases. Originality/value: This paper shows that CEI diffusion is driven by both coercive institutional pressures and inter-firm mimetic mechanisms, including their joint effects. Foreign MNEs act as boundary-spanners that activate a dual isomorphic mechanism, affecting social as well as economic development in host countries. Finally, evidence of interaction between domestic coercive and transnational mimetic mechanisms supports the authors' contention that national institutional fields are increasingly interconnected.